Association Between Somatostatin Receptor Expression and Clinical Outcomes in Neuroendocrine Tumors. Issue 10 (November 2016) - Qian, Zhi Rong; Li, Tingting; Ter-Minassian, Monica; Yang, Juhong; Chan, Jennifer A.; Brais, Lauren K.; Masugi, Yohei; Thiaglingam, Arunthathi; Brooks, Nichole; Nishihara, Reiko; Bonnemarie, Mireille; Masuda, Atsuhiro; et al.
Abstract : Objective: Somatostatin receptors (SSTRs), products of gene superfamily SSTR1 - 5, are commonly expressed in neuroendocrine tumors (NETs). Somatostatin analogs (SSAs) bind to SSTRs and are used as therapeutic agents in patients with advanced NETs. We hypothesized that tumor SSTR expression status would be associated with clinical outcomes in NET. Methods: Expression of the 5 SSTRs was evaluated by immunohistochemistry, using tissue microarrays comprising 173 primary NETs, 24 matched metastases, and 22 metastatic NETs from 195 patients. Cox proportional hazards regression analysis was used to assess the association of SSTR expression status (high vs low) with clinical outcomes, adjusting for potential confounders. Results: High expression of SSTR2 was associated with longer overall survival (OS) in the cohort overall (multivariate hazard ratio, 0.42; 95% confidence interval, 0.21–0.84; P = 0.013). In a subgroup of patients with metastatic small intestine NET treated with SSAs and evaluable for progression, SSTR2 expression was associated with both longer progression-free survival (PFS) and OS. No associations with PFS or OS were observed with expression of other SSTRs. Conclusions: Our study demonstrated that expression of SSTR2, but not other SSTRs, is associated with longer OS. In patients treated with SSAs, expression of SSTR2 is associated with longer PFS survival.